SPOŁECZNO-POLITYCZNY CHARYZMAT PAPIEŻA FRANCISZKA - Kietliński, Krzysztof (Studia Theologica Varsaviensia, 2018)
There are new challenges and dilemmas in today’s world. One of the most important socio-political problems are the poor, immigrants and refugees. God who works in the world sends his servants, giving them a special charisma to indicate the way of solutions. Elected Pope on March 13, 2013. Jorge Mario Bergoglio was given the Holy Spirit. He had the charisma of social sensitivity for compassion for the poor and sinners. Pope Francis recognized his mission as the primary mission of evangelization of the poor, oppressed and marginalized.